Governing the emissive properties of 4-aminobiphenyl-2-pyrimidine push–pull systems via the restricted torsion of N,N-disubstituted amino groups - Cortés-Villena, Alejandro; Soriano-Díaz, Iván; Domínguez, Moisés; Vidal, Matías; Rojas, Pablo; Aliaga, Carolina; Giussani, Angelo; Doménech-Carbó, Antonio; Ortí, Enrique; Galian, Raquel E.; Pérez-Prieto, Julia (Frontiers in Chemistry, 2023)
Donor-acceptor-substituted biphenyl derivatives are particularly interesting model compounds, which exhibit intramolecular charge-transfer because the extent of charge-transfer between both substituents. The connection of 4-[1,1'-biphenyl]-4-yl-2-pyrimidinyl) moiety to differently disubstituted amino groups at the biphenyl terminal can offer push-pull compounds with distinctive photophysical properties. As example, we report here a comprehensive study of the torsion angle of the disubstituted amino group on the emissive properties of two pull-push systems, specifically 4-[4-(4-N,N-dimethylaminophenyl)phenyl]-2,6-diphenylpyrimidine (D1) and 4-[4-(4-N,N-diphenylaminophenyl)phenyl]-2,6-diphenylpyrimidine (D2). The torsion angle of the disubstituted amino group, either N,N-dimethyl-amine or N,N-diphenyl-amine, at the biphenyl end governs their emissive properties. Whereas a drastic fluorescence quenching occurs in D1 as the solvent polarity increases, D2 maintains its emission independently of the solvent polarity. Theoretical calculations on D1 support the presence of a twisted geometry for the lowest-energy, charge-transfer excited state (S1,90), which in polar solvents corresponds to the minimum energy structure and presents a small energy barrier to go from the excited to the ground state, thereby favoring the non-radiative pathway and reducing the fluorescence efficiency. This twisted structure is in contrast absent in D2, due to steric hindrance of the phenyl groups attached to the amine group, making much less favorable the non-radiative decay. Our findings provide insight into the crucial role of the substituent in the donor moiety of Donor-Acceptor systems on both the singlet excited state and the intramolecular charge transfer process.